Liner shipping industry: the impact of strategic alliance on financial performance / Balbino Juanito - Juanito, Balbino (2015)
Strategic alliance is one of the earliest forms of business alliances that emerged in modem history. It is formed to generate benefits that would otherwise not be easily achievable independently. The formation of strategic alliances has been seen as a response to globalization and growing uncertainty in the business environment. Through this collaboration, carriers have the opportunity to achieve economies of scale, increase sailing frequency, reduce cost and business risks, offer quality services, increased direct port calls, and a broader range of customer service options. In today’s highly competitive environment, it is a requirement for the shipping companies to provide low cost, high quality services to meet more demanding customer needs and respond to expanding world-wide markets. Thus, to stay competitive, carriers need to increase services and capitalise in more cost-effective vessels and equipment and all must be achieved within limited resources. The study examined the impact of strategic alliance on Grand Alliance members, particularly on MISC’s financial performance since become a member of the Grand Alliance in 1998. Regression analyses were conducted to test hypotheses on the relationship between vessel utilization and Asia-Europe trade utilization in term of slot capacity with the profit performances of MISC for a period of twenty years from 1990 until 2009. The analyses also conducted on the relationship between vessel utilization, world trade volumes and average bunker price with the revenue of Grand Alliance. The study result shows a significant relationship between MISC’s slot capacity and profit. Similar result recorded for the relationship between MISC’s slot capacity in the Asia- Europe trade and the profit. Nevertheless, there is no significant relationship between slot capacity, world trade volume and average bunker price with the revenue of Grand Alliance. Notably, all variables recorded a sharp declined in 2008 and 2009 due to severe impact of the global economic downturn. Overall, the study results confirmed that strategic alliance has contributed to the financial performance of MISC, where its revenue and profit have improved significantly in tandem with the increases in slot capacity.